EUTHANASIA DALAM PERPEKTIF INDONESIA DAN HAM INTERNASIONAL - Adela Oktaviani Putri; Lina Hastuti (Penerbit Universitas Atma Jaya Yogyakarta, 2026)
The act of euthanasia is a problem that has never been resolved related to the legality of its implementation where many countries have legalized or prohibited the act. Countries that legalize euthanasia impose strict rules regarding the implementation of euthanasia acts. Meanwhile, countries that prohibit the implementation of euthanasia are based on conflicts with religious norms, human rights, and ethics and morals related to the right to life, so euthanasia is prohibited from being carried out. The debate related to the implementation of euthanasia reflects the challenge of balancing human rights with religious and ethical norms. The practice of euthanasia in various countries, both legalized and prohibited, euthanasia is based on humanitarian considerations. The purpose of this research is to analyze the concept of euthanasia from an international human rights perspective with the enactment of euthanasia in various countries that have officially legalized or prohibited it. This research is a normative juridical research with a conceptual approach and a legislative approach. The sources of legal materials used in this study are primary legal materials and secondary legal materials. The results of the study show that the concept of euthanasia enforced in countries that legalize euthanasia such as the Netherlands, Belgium, and the United States is enforced with strict rules and procedures. Countries that prohibit the implementation of euthanasia such as Indonesia do not explicitly regulate euthanasia but use the Criminal Code as a legal basis in terms of prohibiting the practice of euthanasia.